Tiktok Social Media in Pjbl Learning: Tiktok-Based Utilization E-Scaffolding and Effect Towards The Development of Creativity and Communication Skills of Students - Laili Endar Rohmah; Sri Untari; Edi Suhartono (Journal of Educational Sciences, 2025)
The integration of social media into higher education has the potential to enhance students’ creativity and communication skills when supported by appropriate instructional strategies. One such strategy is the use of e-scaffolding in project-based learning (PjBL) to guide students’ learning processes in digital environments. This study aims to describe and analyze the development of students’ creativity and communication skills through the use of TikTok social media based on e-scaffolding within a project-based learning model at the State University of Malang. The research employed a quantitative approach with a descriptive quantitative research design. A pre-experimental method with a one-group pretest–posttest design was used to examine changes in students’ abilities before and after the intervention. Data analysis revealed that the distribution was not normal; therefore, a non-parametric statistical test, namely the Wilcoxon test, was applied. The results showed a significant effect of TikTok-based e-scaffolding on students’ creativity development, with a significance value of 0.012 (p < 0.05). In addition, communication skills also demonstrated a significant improvement, indicated by a significance value of 0.033 (p < 0.05). These findings indicate that the use of e-scaffolding-based TikTok social media in project-based learning significantly contributes to the development of students’ creativity and communication skills.